PEMBELAJARAN MEMBACA AL-QUR’AN DENGAN MENGGUNAKAN METODE QIRO’ATI DI TPQ AL-JIHAD KETAPANG TAHUN 2024 - Iwan, Iwan (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
This research is a field study aiming to examine the preparation, implementation, and challenges in teaching Quranic reading using the Qiro'ati method at TPQ Al-Jihad Ketapang. The data collection methods employed in this study include observation, interviews, and documentation. Data analysis was conducted through four stages: data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that: The preparation for teaching Quranic reading using the Qiro'ati method at TPQ Al-Jihad Ketapang is well-organized, as observed from the teaching preparation carried out by the teachers, such as muraja’ah (review) and ice-breaking activities. The implementation of Quranic reading lessons using the Qiro'ati method at TPQ Al-Jihad Ketapang runs effectively, as shown in the following steps: a. Habit formation. b. Opening activities, which include: 1) greeting, 2) student clapping rhythm (tepuk santri), 3) reciting Surah Al-Fatihah and the prayer before studying, and 4) repetition of readings. c. Core activities consist of: 1) guided reading (baca simak) led by the teacher and 2) student practice in front of the teacher. d. Closing activities involve reciting the khotmil Qur'an prayer, kafaratul majlis prayer, and shalawat busyro. The challenges in teaching Quranic reading using the Qiro'ati method at TPQ Al-Jihad Ketapang can be categorized into internal and external challenges: a. Internal challenges include a lack of understanding of Tajweed rules and students who are not yet familiar with Arabic letters (huruf hijaiyah). b. External challenges include the lack of parental support, limited use of teaching media, and low enthusiasm among students during lessons.